Two new potamid crab species of Potamidae from southern part of Vietnam - Thanh, Dang Ngoc; Hai, Ho Thanh (Academia Journal of Biology, 2015)
Villopotamon gen. nov. Diagnosis Carapace transverse, nearly rectangular. Anterior region lightly swollen, smooth. Latero-posterior region (branchial-cardiac region) densely pubescent. Frontal margin bilobed. Post orbital margin with distinct cristae, post frontal lobes distinctly separated from post orbital margin. Male terminal segment of abdomen triangular, lateral margin straight, slightly longer than VI segment. GO1 terminal segment long 0.4 time length of subterminal segment, distal part filiform. Remarks Villopotamon gen. nov. differs from other known potamid genera of Vietnam and the region by 2 generic aspects: the pubescent latero-posterio region of the carapace surface and the long distal filiform part of the GO1 terminal segment in male. Type species: Villopotamon thaii sp. nov. 1. Villopotamon thaii sp. nov. (Fig. 1, 2) Holotype, 1 male; Allotype, 1 female, collected from the stream at Bana (Quangnam province), Vietnam. Coll. 20 April 2002, deposited in the Zoological Museum, Institute of Ecology and Biological resources, Hanoi-Vietnam. Diagnosis Carapace transverse, nearly rectangular. Frontal part bilobed, anterio-frontal margin concave, rugose. Latero-anterior margin with lateral tooth not developed. Latero-anterior cristae small papulaform. Postorbital margin distinct, slightly curved, postfrontal lobes lightly swollen, rugose. Anterior region (epigastric-hepatic region) smooth. Cervical, semilunar, H-shaped grooves distinct. Latero-posterior region (branchial-csardiac region) densely pubescent. Male terminal segment of abdomen equilateral-triangular with top round, lateral border concave at middle, slightly longer than VI segment. GO1 in male with basal large, distal part tapering, outer border concave. Terminal segment long 0.4 time length of subterminal segment, basal part slightly stout, distal part filiform. Maxiliped III with squarish merus. Ambulatory legs slightly slender with many specimens of Temnocephala sticked fast to. 2. Potamon ungulatum sp. nov. (Fig. 3, 4) Holotype, 1 male; Allotype, 1 female, collected from the stream at Ninhhai, (Ninhphuoc district Ninhthuan province), Vietnam. Coll. on 29 September 2002, deposited in the Zoological Museum, Institute of Ecology and Biological resources, Hanoi-Vietnam. Diagnosis Carapace largely transverse, trapejoid strongly swollen, surface smooth with violet-greenish colour. Frontal part bilobed but anterior margin slightly sinuous, not bilobed. Cervical grooves shallow, semilunar and H-shaped grooves distinct. Postorbital margin sharp, horizontally straight, continuously connected with postfrontal margin. Epibranchial tooth indistinct, anterolateral cristae small papulaform. Male terminal segment of abdomen equilateral-triangular, lateral margin straight, top round. Maxiliped III with rectangular merus, exopod long 1/3 merus. Ambulatory legs short and stout. GO1 in male with subterminal segment strait, distal part gradually tapering. Terminal segment short, unguliform, straight, long 1/4 time length of subterminal segment. Remark Potamon ungulatum sp. nov. is characterized by postorbital margin horizontally straight, continuously connected with postfrontal margin. Dorsal surface quite smooth. Terminal segment short, unguliform, straight. P. ungulatum sp. nov. is closely related to Potamon andersonianum Wood-Mason, 1871, distributed from Burma to Indochina (Rathbun, 1904; Bott, 1970). This new species differs from P. andersonianum in several significant aspects: Dorsal surface quite smooth, postorbital margin horizontally straight. Terminal segment short, unguliform, straight. While others: dorsal surface rugose, postorbital margin no horizontally straight and not connected with postfrontal margin, terminal segment stick-shaped.